RISING STARS mathematics. Year 1, PUPIL Textbook - GLITHRO, LINDA (Rising Stars Wellingborough, 2015)
Exam Board: Non-Specific Level: KS1 Subject: Mathematics First Teaching: September 2015 First Exam: Summer 2017 The full-colour, engaging Textbook for Year 1 is designed to aid high-quality teaching and learning. Characters introduce and discuss a common misconception for each concept, supported by visual representations. A set of practice activities is provided per concept, offering bare practice, through to practice in context and then open-ended investigation, to build conceptual understanding. This textbook has been written and reviewed by mathematics experts with extensive classroom exper